The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1353/ajm.2003.0040
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics, frequency modulation, and low regularity ill-posedness for canonical defocusing equations

Abstract: In a recent paper [18], Kenig, Ponce and Vega study the low regularity behavior of the focusing nonlinear Schrödinger (NLS), focusing modified Korteweg-de Vries (mKdV), and complex Korteweg-de Vries (KdV) equations. Using soliton and breather solutions, they demonstrate the lack of local well-posedness for these equations below their respective endpoint regularities.In this paper, we study the defocusing analogues of these equations, namely defocusing NLS, defocusing mKdV, and real KdV, all in one spatial dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
465
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(479 citation statements)
references
References 39 publications
(112 reference statements)
7
465
3
1
Order By: Relevance
“…In this paper, we prove GWP for k = 0, s = − 1 2 , using a scheme based on mass conservation (1.2) and subcritical slack in certain multilinear estimates at this regularity threshold. In [12], it is shown that the onedimensional LWP theory of [11] is effectively sharp by adapting techniques of [5] and [7]. Thus, we establish GWP in the largest space for which LWP holds.…”
Section: Introductionmentioning
confidence: 95%
“…In this paper, we prove GWP for k = 0, s = − 1 2 , using a scheme based on mass conservation (1.2) and subcritical slack in certain multilinear estimates at this regularity threshold. In [12], it is shown that the onedimensional LWP theory of [11] is effectively sharp by adapting techniques of [5] and [7]. Thus, we establish GWP in the largest space for which LWP holds.…”
Section: Introductionmentioning
confidence: 95%
“…In his work, of particular importance is the gauge transformation defined by 6) with J (f )(x) :=´x −∞ |f (y)| 2 dy, x ∈ R. Through the transformation v = G 1 2 (u), DNLS reduces to i∂ t v + ∂ 2 x v = i|v| 2 ∂ x v (1.7) and the theory of [45] for smooth initial data with sufficiently small H 1 -norm can be applied. This result was improved in the papers by Hayashi and Ozawa [15,16] by reducing DNLS to a system of two semi-linear Schrödinger equations (with no derivatives in the nonlinearities), where it was obtained 3 the global existence of H 1 -solutions under the assumption while the norms of interest remain essentially unchanged, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…After the works of [23], [1] and [13] gathering the local and the global well-posedness results, in [15], [2], [16], [3], [4], [25], [11], [12] and [17] one has:…”
Section: Introductionmentioning
confidence: 99%